STRUKTUR KOMUNITAS MOLUSKA DI ESTUARI DESA BAGAN ASAHAN KECAMATAN TANJUNG BALAI KABUPATEN ASAHAN - Ilham Syahputra; Ipanna Enggar Susetya (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Tanjung Balai is one of the regions in North Sumatera which has marine potential in the form of molluscs. Tanjung Balai waters are adjacent to the Malacca Strait. Estuari waters in Bagan Asahan are very rich in potential biota in the form of molluscs. This research was conducted in April to May 2018 in the Estuari Waters of Bagan Asahan Village. Mollusc sampling was carried out at three different stations with three points of retrieval and three times repetitions. Station I was located in the area of mangrove forest zone, station II was located near community and station III was located on the estuari. The results showed that 1.276 individuals consisting of 2 classes, 14 families and 20 species. The abundance of mollusc species in the three research stations ranged from 499 ind/m3 - 2148 ind/m3. The highest relative abundance value was found in Meretrix meretrix mollusc species with the value of 63.2% at station III. Diversity Index (H ') ranged from 0.926 to 2.325 classified as low to moderate, Uniformity (E) ranged from 0.476 to 0.789 classified as moderate to high, Dominance (C) ranged from 0.049 to 0.900 classified as low to high. The results of measurements of water chemistry physical parameters are still at a reasonable threshold for the life of molluscs. Physical and chemical parameters that are positively correlated with abudance are temperature, depth, salinity and organic matter. Physical and chemical parameters that are negatively correlated with abundance are brightness, pH, DO, salinity and phosphate.Keywords: Community Structure, Molluscs, Estuari, The Environment